Effect of a 12-Week Training Program on Levels of Glucose-6-Phosphate Dehydrogenase and Antioxidant Activity - Murat Kaldırımcı (Archives of Rheumatology, 2010)
Objective: It has been suggested that regular, long- term exercise increases erythrocyte glucose-6- phosphate dehydrogenase (G6PD) and antioxidant enzymatic activities. The purpose of this study was to investigate whether G6PD activity and antioxidant activities consisting of glutathione peroxidase (GPX) and glutathione s transferase (GST) levels changed with a 12 week aerobic exercise program in basketball players. Materials and Methods: For baseline values, blood samples were obtained from basketball players and age and sex matched sedentary healthy volunteers. Plasma GPX, GST levels and G6PD activities were evaluated with commercial kits. Then, a 12 week training program was performed for basketball players. Pre training and post training values were compared within all groups. Results: Before training program, GPX, GST levels and G6PD activities were significantly higher in basketball players than sedentary controls (p<0.05, p<0.05, p<0.001, respectively). Also G6PD activities and GPX, GST levels were significantly increased after training program. (p<0.05, p<0.01, p<0.01, respectively). A positive correlation was found between G6PD activity and GPX, GST levels. Conclusion: Our results suggest that long term- regular physical exercise increases G6PD activity and antioxidant activities and cause adaptations in antioxidant defences. (Turk J Rheumatol 2010; 25: 34-6)